Implementasi Kegiatan Pembelajaran Bahasa Arab Pada Boarding School SMA Muhammadiyah 2 Sidoarjo - Sari, Renita; Hikmah, Khizanatul (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2024)
This research discusses the implementation of Arabic language learning using the boarding school system at SMA Muhammadiyah Sidoarjo, which discusses learning planning, namely an Arabic learning plan including activities to develop learning objectives and planning the flow of lessons for learning Arabic, implementation of learning, namely learning plans. that have been developed, as well as a continuous process of teaching and learning activities that focus on school activities to achieve educational goals, learning evaluation is one of the important stage activities that educators must carry out to determine the effectiveness and efficiency of learning. In the Arabic language learning planning at Muhammadiyah Sidoarjo High School, currently there is a learning curriculum, learning tools and an Arabic language competency skills upgrading program implemented for teachers and students. In the learning implementation there is formal and non-formal learning. Evening diniyah formal learning. Meanwhile, non-formal learning takes the form of giving mufrodat, muhadoroh, and language drama. In learning evaluation there are 3 assessment components, namely daily assessment, daily test assessment and final pre-school assessment which are test and non-test based.